Platelet-Activating Factor Acetylhydrolase Expression in BRCA1 Mutant Ovarian Cancer as a Protective Factor and Potential Negative Regulator of the Wnt Signaling Pathway - Yue Liao; Susann Badmann; Till Kaltofen; Doris Mayr; Elisa Schmoeckel; Eileen Deuster; Mareike Mannewitz; Sarah Landgrebe; Thomas Kolben; Anna Hester; Susanne Beyer; Alexander Burges; et al. (Biomedicines, 2021)
Aberrantly activated Wnt/β-catenin signaling pathway, as well as platelet-activating factor (PAF), contribute to cancer progression and metastasis of many cancer entities. Nonetheless, the role of the degradation enzyme named platelet-activating factor acetylhydrolase (PLA2G7/PAF-AH) in ovarian cancer etiology is still unclear. This study investigated the functional impact of platelet-activating factor acetylhydrolase on BRCA1 mutant ovarian cancer biology and its crosstalk with the Wnt signaling pathway. PAF-AH, pGSK3β, and β-catenin expressions were analyzed in 156 ovarian cancer specimens by immunohistochemistry. PAF-AH expression was investigated in ovarian cancer tissue, serum of BRCA1-mutated patients, and in vitro in four ovarian cancer cell lines. Functional assays were performed after PLA2G7 silencing. The association of PAF-AH and β-catenin was examined by immunocytochemistry. In an established ovarian carcinoma collective, we identified PAF-AH as an independent positive prognostic factor for overall survival (median 59.9 vs. 27.4 months; p = 0.016). PAF-AH correlated strongly with the Wnt signaling proteins pGSK3β (Y216; nuclear: cc = 0.494, p < 0.001; cytoplasmic: cc = 0.488, p < 0.001) and β-catenin (nuclear: cc = 0.267, p = 0.001; cytoplasmic: cc = 0.291, p < 0.001). In particular, high levels of PAF-AH were found in tumor tissue and in the serum of BRCA1 mutation carriers. By in vitro expression analysis, a relevant gene and protein expression of PLA2G7/PAF-AH was detected exclusively in the BRCA1-negative ovarian cancer cell line UWB1.289 (p < 0.05). Functional assays showed enhanced viability, proliferation, and motility of UWB1.289 cells when PLA2G7/PAF-AH was downregulated, which underlines its protective character. Interestingly, by siRNA knockdown of PLA2G7/PAF-AH, the immunocytochemistry staining pattern of β-catenin changed from a predominantly membranous expression to a nuclear one, suggesting a negative regulatory role of PAF-AH on the Wnt/β-catenin pathway. Our data provide evidence that PAF-AH is a positive prognostic factor with functional impact, which seems particularly relevant in BRCA1 mutant ovarian cancer. For the first time, we show that its protective character may be mediated by a negative regulation of the Wnt/β-catenin pathway. Further studies need to specify this effect. Potential use of PAF-AH as a biomarker for predicting the disease risk of BRCA1 mutation carriers and for the prognosis of patients with BRCA1-negative ovarian cancer should be explored.